The Handling of Tidal Flood (Rob) with polder system - Ikhwanudin Ikhwanudin (International Conference on Coastal and Delta Areas, 2017)
Rain often causes inundations in the area of Semarang. Currently,drainage system in the area of East Semarang is strongly influenced by the presence of tidal water. It causes the social and economic losses due to the inundation of rob that floods the northern coast of Central Java. Therefore, some studies are necessary to overcome the problem of flood and rob that exist. The mitigations of tidethat get on the land (called rob) are also needed. To remove the flood of East flood canal Normalization (BKT), Tenggang River and Sringin River, pumps with detention pond are required. Modeling designis done by using HEC-RAS application program for modeling river water flow, and RiverAnalysis System (RAS), which is created and developed by Hydrologic Engineering Center (HEC). The appropriate flood control and handling systems are polder systems, with the infrastructure components of sea dams utilized as protection against tide (rob) towards the mainland of Tenggang River watershed and Sringin River watershed. The rainwater expenditure falling in the watershed uses pumps and detention ponds. Keywords: Polder, Drainage City, Dam